Identification of the KDM2/7 histone lysine demethylase subfamily inhibitor and its antiproliferative activity. - Suzuki, T; Ozasa, H; Itoh, Y; Zhan, P; Sawada, H; Mino, K; Walport, L; Ohkubo, R; Kawamura, A; Yonezawa, M; Tsukada, Y; Tumber, A; et al. (2013)
Histone N(ε)-methyl lysine demethylases KDM2/7 have been identified as potential targets for cancer therapies. On the basis of the crystal structure of KDM7B, we designed and prepared a series of hydroxamate analogues bearing an alkyl chain. Enzyme assays revealed that compound 9 potently inhibits KDM2A, KDM7A, and KDM7B, with IC50s of 6.8, 0.2, and 1.2 μM, respectively. While inhibitors of KDM4s did not show any effect on cancer cells tested, the KDM2/7-subfamily inhibitor 9 exerted antiproliferative activity, indicating the potential for KDM2/7 inhibitors as anticancer agents.